2012
DOI: 10.1590/s0001-37652012000300024
|View full text |Cite
|
Sign up to set email alerts
|

Seed reserve composition and mobilization during germination and early seedling establishment of Cereus jamacaru D.C. ssp. jamacaru (Cactaceae)

Abstract: Cereus jamacaru, a Cactaceae found throughout northeast Brazil, is widely used as cattle food and as an ornamental and medicinal plant. However, there has been little information about the physiological and biochemical aspects involved in its germination. The aim of this study was to investigate its reserve mobilization during germination and early seedling growth. For this, C. jamacaru seeds were germinated in a growth chamber and collected at 0, 2, 4, 5, 6, 8 and 12 days after imbibition for morphological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
(12 reference statements)
1
31
0
3
Order By: Relevance
“…Oleic acid was also the most common monounsaturated fatty acid found in samples of several species of vegetables and cereals, and their amount was decreased in most of the germinated samples (Megat-Rusydi et al 2011). Furthermore, it is possible that the mobilization and reduction of the lipids during seed germination of C. jamacaru related by Alencar et al (2012) may be due to the consumption of oleic acid during the processes of germination and formation of the mandacaru seedlings. Thus, the oleic acid that is found in larger quantities in the seeds of mandacaru of both localities Maringá and Picos may explain the non significant difference in the rate of seed germination from the South and Northeast regions of Brazil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oleic acid was also the most common monounsaturated fatty acid found in samples of several species of vegetables and cereals, and their amount was decreased in most of the germinated samples (Megat-Rusydi et al 2011). Furthermore, it is possible that the mobilization and reduction of the lipids during seed germination of C. jamacaru related by Alencar et al (2012) may be due to the consumption of oleic acid during the processes of germination and formation of the mandacaru seedlings. Thus, the oleic acid that is found in larger quantities in the seeds of mandacaru of both localities Maringá and Picos may explain the non significant difference in the rate of seed germination from the South and Northeast regions of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…We suspect that the procedure used to germinate seeds of C. peruvianus from the South region of Brazil may be also used to seed germination of the mandacaru plants from Northeast. Therefore, one of our aims on this study was to analyze and compare the germination rates of seeds from mandacaru plants maintained in the two contrasting edaphoclimatic regions (Northeast and South of Brazil), and moreover investigate differences in the concentration and chemical composition (Alencar et al 2012). The pattern of isozymes related with the fatty acids metabolism in seeds, such as lipases, was also analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes of starch and protein digestion i.e., α, β-amylase and protease are accountable for breakdown and mobilization of these major reserve materials of seeds (Alencar et al, 2012). The maximum retarded activity of enzymes was observed when Cd was applied @ 450 mg/kg while both the chelators especially OA helped in relieving the toxic effects of Cd on both hydrolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Paula et al (2016) found that lipids and protein bodies inside the endosperm cells of Morinda citrifolia served as the main reserve components. In Cereus jamacaru, Alencar et al (2012) discovered that lipids were the main reserve in seeds that were stored in cotyledons while soluble sugar and starch were the minor reserves. In Jatropha curcas seeds, it was determined that the endosperm lipids represent the most abundant reserve and proteins were the secondmost important reserve (Alencar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%